Study on Coagulation Characteristics of Drinking Water Sources in Upper Yangtze River - Xiang, Ping; Zhang, Zhi; Jiang, Shaojie; Zhang, Ying (Asian Journal of Chemistry, 2014)
A series of coagulants such as polyaluminum chloride (PAC), polymeric ferric sulfate (PFS), aluminum sulfate (AS) and ferric chloride (FC), as well as the composite coagulants which composed with polydimethyldiallylammonium chloride (PDADMAC) were used to treat drinking water sources in the upper Yangtze river at Chongqing. pH and temperature as the two significant factors were tested. The results showed that the coagulation effect by coagulants composed with PDADMAC was improved greatly. The work of turbidity removal was good, and the effect of organics removal was poor when pH in the raw water was stable. By modifying the pH to 5, the better organics removal ratio was achieved when aluminum-based coagulants were used. Analogously when the pH ranged from 4 to 6, the better organics removal ratio was also achieved by using iron-based coagulants. When the pH was beyond 11, the organics removal ratio improved remarkably. In different seasons, the feature of raw water quality played a more important role than temperature in coagulation effects. Optimization of coagulant would be the suitable enhanced coagulation technology for current water treatment process in Chonqing.